Coverage Changes and Earnings Forecast Accuracy. (October 2019) - Cheong, Foong Soon; Lee, Changhee; Palmon, Dan
We examine the effect on earnings forecast accuracy when financial analysts add or drop coverage. We find that the accuracy of analysts' first forecast for a firm (newly added coverage) is lower relative to their peers. In addition, the accuracy of their last forecast (just before coverage is dropped) is lower relative to their peers. Further analysis shows that our results are not driven by the rookie analysts (analysts with less than 1-year experience) or retiring analysts (i.e., analysts who are within their final year before retiring).